In vitro antimicrobial efficacy of a fixed-dose combination of RHZE against M. tuberculosis - Vanessa Albertina Agertt; Pauline Cordenonsi Bonez; Caren Rigon Mizdal; Grazielle Guidolin Rossi; Vanessa da Costa Flores; Marli Matiko Anraku de Campos
ABSTRACT The use of drugs in fixed-dose combination (FDC) is now recommended by the World Health Organization (WHO) due to the emergence of multidrug-resistant strains of Mycobacterium tuberculosis. FDC uses different drugs against tuberculosis (TB) in a single tablet for phase-intensive therapeutic intervention. This therapy aims to optimize treatment, to prevent inappropriate use of drugs, and to prevent the emergence of new resistant strains. This study aims to evaluate the susceptibility of clinical isolates of M. tuberculosis against rifampicin, isoniazid, ethambutol, and pyrazinamide. The antimicrobials were tested separately and in associations according to FDC. This was used for broth microdilution method, which was compared to the proportions method previously considered as the gold standard. In antimicrobials testing alone, several strains were resistant to one, two, or three drugs. However, when applied to association of drugs in FDC, there was no antimicrobial resistance. The results strengthen the FDC's concept, which aims to unite the four anti-TB drugs to combat bacterial resistance.